Profiling the antidiabetic potential of compounds identified from fractionated extracts of Entada africana toward glucokinase stimulation: computational insight - Onikanni, Sunday Amos; Lawal, Bashir; Munyembaraga, Valens; Bakare, Oluwafemi Shittu; Bakhtiar, M. Taher; Khotib, Junaidi; Darnis, Deny Susanti; Oyinloye, Babatunji Emmanuel; Noriega, Lloyd; Famuti, Ayodeji; Fadaka, Adewale Oluwaseun; Ajiboye, Basiru Olaitan (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Abstract: Glucokinase plays an important role in regulating the blood glucose level and serves as an essential therapeutic target in type 2 diabetes management. Entada africana is a medicinal plant and highly rich source of bioactive ligands with the potency to develop new target drugs for glucokinase such as diabetes and obesity. Therefore, the study explored a computational approach to predict identified compounds from Entada africana following its intermolecular interactions with the allosteric binding site of the enzymes. We retrieved the three-dimensional (3D) crystal structure of glucokinase (PDB ID: 4L3Q) from the online protein data bank and prepared it using the Maestro 13.5, Schrödinger Suite 2022-3. The compounds identified were subjected to ADME, docking analysis, pharmacophore modeling, and molecular simulation. The results show the binding potential of the identified ligands to the amino acid residues, thereby suggesting an interaction of the amino acids with the ligand at the binding site of the glucokinase activator through conventional chemical bonds such as hydrogen bonds and hydrophobic interactions. The compatibility of the molecules was highly observed when compared with the standard ligand, thereby leading to structural and functional changes. Therefore, the bioactive components from Entada africana could be a good driver of glucokinase, thereby paving the way for the discovery of therapeutic drugs for the treatment of diabetes and its related complications.